SISTEM PENGAMBILAN KEPUTUSAN PERCERAIAN DI PENGADILAN NEGERI KOTABUMI DENGAN METODE SAW - Nurmayanti Nurmayanti; Merri Parida; Desi Malina (Jurnal informasi dan komputer, 2022)
Divorce is an event or event of a bad marriage adjustment, namely the breaking of the marriage bond between a man and a woman as husband and wife. While the meaning of divorce according to civil law is the abolition of marriage by a judge's decision on the demands of one of the parties in the marriage. Divorce that is carried out usually still applies a system of mutual deliberation by both parties so that there is no application or use of a method and also there is no application of a divorce decision-making system that is applied. Several criteria were set, namely Domestic Violence, Ignoring Responsibility, Infidelity, Disputes, Narcotics, Committing Crimes, and determining the weight of each criterion to obtain the final score for each alternative. The system development method used is the Extreme Programming method. And the system development tools are Use Case Diagrams, Activity Diagrams, Class Diagrams. The results of this study the author can make a Divorce Decision Making System application at the Kotabumi District Court u sing the web-based SAW (Simple Additive Weighting) method which can provide a solution in decision making to determine a married couple who filed a suit that deserves to be divorced.